Conversational Implicature in Qur'anic Narratives: The Story of Moses, Peace Be Upon Him, and the Righteous Servant as a Model - Emad Ahmed, Lect. Dr. Raid (Basra studies journal, 2024)
This research addresses the phenomenon of conversational implicature in Qur'anic discourse by examining the story of Prophet Moses (peace be upon him) and the righteous servant in Surah Al-Kahf. The study focuses on analyzing the implicit meanings conveyed by specific structural and declarative expressions, as well as their pragmatic purposes, within their contextual and communicative settings. Drawing upon various interpretations and scholarly opinions, the researcher aims to apply pragmatic analysis to the dialogue texts in the story of Moses and the righteous servant. Special attention is given to the objectives and messages embedded within the Qur'anic dialogue.